2019
DOI: 10.1140/epjd/e2019-100052-y
|View full text |Cite
|
Sign up to set email alerts
|

Soliton-comb structures in ring-shaped optical microresonators: generation, reconstruction and stability

Abstract: Characteristic features of soliton-comb structures in optical microresonators are investigated in normal and anomalous dispersion regimes, when the detuning parameter is varied over a broad range of values. The study rests on the assumption that soliton combs are self-organized ensemble of co-propagating coherently entangled states of light, and depending on the group-velocity dispersion they can result from space-division multiplexing of single-bright and singledark solitons. Their analytical and numerical re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…The decay of metastable states over an energy barrier is a physical process inherent to a large number of systems, and particularly those undergoing phase transitions [51,52,53]. It is observed in the motion of atoms trapped in the field of force of a multi-well potential [52], the motion of kinks and dislocations across the Peierls-Nabarro barrier [54,55], the excitations of Cooper pairs in a Josephson loop [56], the dynamics of macromolecules in DNA strands and other molecular chains across hydrogen bridges and so on. In a pioneer study Kramers [51] suggested that the lifetime of a classical particle in a metastable state, separated from a stable equilibrium state by an energy barrier, would obey Arrhenius law.…”
Section: Discussionmentioning
confidence: 99%
“…The decay of metastable states over an energy barrier is a physical process inherent to a large number of systems, and particularly those undergoing phase transitions [51,52,53]. It is observed in the motion of atoms trapped in the field of force of a multi-well potential [52], the motion of kinks and dislocations across the Peierls-Nabarro barrier [54,55], the excitations of Cooper pairs in a Josephson loop [56], the dynamics of macromolecules in DNA strands and other molecular chains across hydrogen bridges and so on. In a pioneer study Kramers [51] suggested that the lifetime of a classical particle in a metastable state, separated from a stable equilibrium state by an energy barrier, would obey Arrhenius law.…”
Section: Discussionmentioning
confidence: 99%
“…In this case the 'tanh' soliton solution of the GP equation becomes unstable. However besides this hyperbolic kink-soliton solution, the Nonlinear Schrödinger equation with self-defocusing nonlinearity can also admit a periodic-soliton structure which is represented by a Jacobi elliptic function [29,32,35,36]. This last periodic solution is the kind of soliton structure we are interested in, in connection with its periodic feature we can readily assume that it forms in a BEC with a ring shape of effective length L. Seeking for the periodic-soliton solution of the GP equation ( 1), we consider a wave function that describes a stationary state.…”
Section: The Model and Matter-wave Periodic Dark Soliton Solution For...mentioning
confidence: 99%
“…Assuming the BEC to be of finite length L, the application of periodic boundary conditions favored soliton solutions represented by the Jacobi Elliptic function of the snoidal type. In [32], we established that the snoidal function is a 'crystal' of 'tanh-shaped kink-antikink' solitons. Using the matter-wave dark soliton crystal found, the linear Schrödinger equation for the free boson gas was shown to reduce to the Lamé equation of an arbitrary order ν.…”
Section: Summary and Concluding Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…Substituting this in Equation (), we find that the wave amplitude A()t must obey the first‐integral equation: At=ζ()A4sζA2+ρ1, with ρ1 an energy constant determining shape profile of A()t. Solving Equation () with periodic boundary conditions, 33–36 the pump amplitude A()t is found to be the following nonlocalized periodic pattern of time‐entangled dark solitons: A()t=Qζitalicsn[]Q()tt0, where italicsn() is a Jacobi elliptic function of modulus κ (with 0κ1), and: Q=s()1+κ2,2ems=kω2. The amplitude A()t of the periodic dark soliton () is represented in Figure 1, for κ=0.98 (left graph) and κ=1 (right graph). Note that when κ1 the Jacobi elliptic function italicsn() italictanh() , corresponding to the dark soliton pump obtained in Ref.…”
Section: The Pump‐probe Equations and Dark‐soliton‐crystal Solution To The Pump Equationmentioning
confidence: 99%